1989
DOI: 10.1093/nar/17.20.8061
|View full text |Cite
|
Sign up to set email alerts
|

Direct demonstration of termination signals for RNA polymerase II from the sea urchin H2A histone gene

Abstract: Previous studies [1,2] suggested but did not prove that the sea urchin H2A histone gene possesses strong transcriptional termination signals close to, but separate from, the 3' processing signals. In this study we have demonstrated by two independent approaches that these sequences elicit authentic transcriptional termination. First we show by nuclear run off analysis that nascent transcription terminates in the immediate 3' flanking region of the H2A gene, in an A-rich region. Second we show that these termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In both systems the termination site does not require a histone 3'-processing signal. The termination site which they defined is capable of blocking expression of a human gene in the absence of the histone 3'-processing signal, suggesting that this is an intrinsic termination signal (8). The physiological significance of this sequence is not clear, given the heterologous nature of these experiments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In both systems the termination site does not require a histone 3'-processing signal. The termination site which they defined is capable of blocking expression of a human gene in the absence of the histone 3'-processing signal, suggesting that this is an intrinsic termination signal (8). The physiological significance of this sequence is not clear, given the heterologous nature of these experiments.…”
Section: Discussionmentioning
confidence: 96%
“…They suggested that termination of transcription in the sea urchin H2a gene injected into Xenopus oocytes occurred about 200 nt downstream of the gene. This same sequence has been shown to terminate transcription of heterologous genes in mammalian cells in the absence of a 3'-processing signal (8,25), suggesting that the mechanism of transcription termination may differ between histone genes and genes encoding polyadenylated mRNAs.…”
mentioning
confidence: 89%
“…Cytoplasmic RNA was purified by centrifugation through a sucrose cushion, phenol-chloroform extraction and ethanol precipitation. S1 analysis was carried out as described [28], using a 3'end-labeled double-strand DNA probes as described in Fig. 2.…”
Section: Transfection and S1-nuclease Analysismentioning
confidence: 99%
“…In addition to the wellstudied effects in c-myc, which formed the starting point for our work, similar mechanisms appear to control transcription of c-myb (3), c-mos (48), c-fos (18,50), L-myc (36), and the adenosine deaminase gene (14). Premature (12,15), and in small nuclear RNA (snRNA) genes (28,54). However, no consensus sequence for a pol II termination site has emerged from these studies.…”
mentioning
confidence: 92%